Sertoli cells: immunomodulatory properties, methods of isolation and culture - N. N. Skaletskiy; G. N. Skaletskaya (Вестник трансплантологии и искусственных органов)
Due to complications caused by the inevitable use of immunosuppressive drugs in organ and cell transplantation, the use of natural mechanisms of immunological tolerance identified in animal and human organisms arouses interest. It has long been known that there are certain areas in them, including the testis, where immune reactions are virtually impossible. Our review focuses on the role of Sertoli cells that provide testicular immune privilege. Methods of isolation and cultivation of Sertoli cells are described and their potentials in biology and medicine are discussed.